Legal Protection for Heirs in a Dispute Over a Shophouse Sale and Purchase Agreement - Panji Maulana; Muhammad Insa Ansari; Teuku Saiful (International Journal of Law and Society, 2025)
Basically, heirs have the same legal position as the testator in agreement disputes, including sale and purchase agreements made before the testator dies. However, in practice, there is often a discrepancy between the legal provisions and their implementation, especially when there is a conflict between the heirs and third parties. This can be seen in the dispute between Baniyamin as the buyer and the heirs of Muhammad Husen, where the shophouse sale and purchase agreement ended with a default on the part of the seller, so that the responsibility to provide compensation was imposed on the heirs. This research aims to analyse the legal position of the heirs in a dispute over a sale and purchase agreement involving the heir's estate and the form of legal protection that should be given to the heirs. This research uses normative juridical research and case study approach. Data analysis uses a qualitative method. The results show that the position of the heirs is found in the saisine principle in Article 833 of the Civil Code, the rights and obligations of the testator automatically pass to the heirs. The legal protection of heirs is regulated in Articles 833, 1045, and 1100 of the Civil Code, which provide the right to inheritance with debt responsibility limited to the value of the inheritance and the right to refuse harmful inheritance.